Influence of repeated contacts on the transfer of elemental metallic lead between compartments in an integrated conceptual model for dermal exposure assessment. Issue 3 (1st February 2022) - Sahmel, J.; Arnold, S.; Ramachandran, G.
ABSTRACT: Transfer of contaminants to and from the skin surface has been postulated to occur through a number of different pathways and compartments including: object(s)-to-skin, skin-to-skin, skin-to-clothing, skin-to-gloves, air-to-skin, skin-to-lips, and skin-to-saliva. However, many identified transfer pathways have been only minimally examined to determine the potential for measurable transfer. The purpose of this study was to quantitatively evaluate repeated transfer between different compartments using elemental metallic lead (Pb) in the solid form using a series of systematic measurements in human subjects. The results demonstrated that some transfer pathways and compartments are significantly more important than others. Transfer of Pb could not be measured from skin to cotton clothing or skin to laminate countertop surfaces. However, transfer was consistently measured for skin-to-skin and between the skin and the surface of nitrile gloves, suggesting the potential for significant transfer to or from these compartments in real-world exposure scenarios, and the importance of these pathways. With repeated contacts, transfer increased non-linearly between 1 and 5 contacts, but appeared to approach a steady state distribution among the compartments within 10 contacts. Consistent with other studies, relative to 100% transfer for a single contact, the quantitative transfer efficiency decreased with repeated contacts to 29% after 5 contacts and 11–12% after 10 contacts; for skin-to-skin transfer measurements, transfer efficiency after either 5 or 10 contacts was approximately 50% of the single contact transfer. These data are likely to be useful for refining current approaches to modeling of repeated contacts for dermal exposure and risk assessment.